v.2 - Rayudu, C.S. (Delhi, 1989)
The new strategy of agricultural development began effectively only after the launch of Five Year Plans. Agricultural development alone, however, does not mean the whole rural development. It cannot be assumed co-terminus with agriculture. But it is a mix of varied allied rural economic sectors such as dairying, milk supply, forestry, fisheries, livestock, animal husbandry, poultry, piggery etc. The group of beneficiaries involved in the process are agricultural labourers, Jandless labourers, artisans of various trades, small farmers, marginal farmers, bonded labour, SCs. & STs. and other poverty striken section. A multi-dimensional approach is recessary for integrated development. A number of special rural development programmes have been formulated and implemented towards this end. The special feature of the book is that it takes in its sweep every sector of rural economy in its scope to make this work as comprehensive as possible. It emphasises Five Year Plans, State efforts, role of RBI,NABARD, NADC, ARDC and other development agencies. It endeavours to study with reference to plan objectives, strategies adopted, financial and physical targets set and actual achievements in various rural economic sectors. It also covers different adminiSin authorities, departments managing the zura: developmental activities. in this book the author makes an attempt to examine the multi-various aspects of rural development. This book is aimed to introduce the reader to the vital areas of the rural development facing today. The present pioneering and indepth study is the outcome of the author's wide thinking and painstaking survey. The book "Management of Rural Development(3y (Bis most useful to the planners, policy makers, administrators, scholars, researchers, students in the field of rural economics and as a compendium on the subject of rural development.s
Keywords: Rural Development Management